Development Problems of Social Entrepreneurship in Kazakhstan - BAUER, Maira Sh.; MUSSINA, Raushan S.; BENCHEVA, Nelly A.; OVCHINNIKOVA, Tatyana V.; AMERKHANOVA, Indira K. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).03, 2018)
Currently, the development dynamics of the market and socio-economic relations require creating hybrid forms of organizations, able to fill the market niches and to intervene when the state cannot fulfill its obligations. In this sense, social entrepreneurship is a popular term that encompasses a wide range of structures and organizations, running the business in order to achieve certain social impact. It should be understood that social entrepreneurship is not a project, but business, business of dual nature: entrepreneurship with strong social impact. The stages of development of the theoretical approaches to social entrepreneurship are presented in this article. Some issues of the formation of social entrepreneurship in Kazakhstan are considered. The main obstacles to the development of social entrepreneurship in Kazakhstan are the disparity of information on social entrepreneurship, the lack of consulting services, criteria and support mechanisms, public information on state tenders and contact details. Meanwhile, the development of social entrepreneurship in Kazakhstan is becoming an important activity for all stakeholders - the entrepreneurs, the state, and the society. Social entrepreneurs can become reliable partners of the state in solving the social problems in the country. They will be able to solve the social problems of the population in a qualitative way, simultaneously saving the budget funds allocated for the social sphere.